2013
DOI: 10.1021/es402204y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Comparison of PBDEs, OH-PBDEs, PCBs, and OH-PCBs in the Serum of Second Trimester Pregnant Women Recruited from San Francisco General Hospital, California

Abstract: Prenatal exposures to polybrominated diphenyl ethers (PBDEs) can harm neurodevelopment in humans and animals. In 2003–2004, PentaBDE and OctaBDE were banned in California and phased-out of US production; resulting impacts on human exposures are unknown. We previously reported that median serum concentrations of PBDEs and their metabolites (OH-PBDEs) among second trimester pregnant women recruited from San Francisco General Hospital (2008–2009; n=25) were the highest among pregnant women worldwide. We recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 55 publications
8
93
4
Order By: Relevance
“…A study from the US with slightly lower median serum PCB concentrations compared to the present study (Table 6) found downward trends of PCB74, PCB118, PCB138, PCB153, and PCB180 in US pregnant women between 2008-2012(Zota et al 2013.…”
Section: Temporal Trends Of Lipophilic Popscontrasting
confidence: 68%
“…A study from the US with slightly lower median serum PCB concentrations compared to the present study (Table 6) found downward trends of PCB74, PCB118, PCB138, PCB153, and PCB180 in US pregnant women between 2008-2012(Zota et al 2013.…”
Section: Temporal Trends Of Lipophilic Popscontrasting
confidence: 68%
“…Likewise, in our cross-sectional analysis, serum concentrations of PCBs 118 and 138 decreased with sampling date during the study period (2006–2007). Moreover, when compared to other studies of PCBs in sera from California adults, our results are consistent with a decreasing trend over time, for example our median PCB-153 concentration (9.7 ng/g lipid) is lower than that for samples collected in the 1960s (73 ng/g lipid) and 1990s (41 ng/g lipid) (Petreas, et al 2003) and higher than that for samples collected from 2008–2009 (3.8 ng/g lipid) and 2011–2012 (3.1 ng/g lipid) (Zota, et al 2013). Wolff et al (Wolff, et al 2005) postulated that in populations where POP uptake is ongoing, the dilution effect of high adiposity results in an inverse relationship between BMI and POP-serum concentrations; whereas, in populations where current POP uptake is negligible, POPs trapped in adipose tissues are released more slowly in normal weight women than in overweight women, resulting in a positive relationship between BMI and POP-serum concentrations.…”
Section: Discussionsupporting
confidence: 84%
“…As new policies started to be implemented in CA almost 10 years ago to ban and restrict PBDE commercial mixtures, our recent human population study reported that serum PBDE levels declined 39% from 2008−2009 to 2011−2012 in CA women. 13 Similar PBDE declines were also observed in other studies from Australia, European, and Asian countries in humans and in fish. 14−16 However, an uncertain trend (downward, then upward) was found in marine animals (shrimp, common carp, and yellow catfish) from East China in 2009−2012.…”
Section: ■ Introductionsupporting
confidence: 82%
“…The consistent findings in both HT and non-HT cat groups as well as the combined cat group confirmed the declines reported in our previous human population study. 13 These declines in human and house cats are probably due to the ban of penta-BDE and octa-BDE in 2004, as well as the voluntary ban/restricted production of deca-BDE in CA, 39 suggesting the efficacy of regulatory policies. A similar decline was also reported in 12 pools of Australian human milk collected between 1993 and 2009.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%